The Role of Lembaga Tabung Haji in Hajj Management in Malaysia: An Overview - Ismail, Sharifah (Medwell Publishing, 2020)
The purpose of this paper is to examine the hajj institution in Malaysia and its management features. It also highlights the conduct of hajj from Malaysia with special reference to the position and roles of Tabung Haji on the hajj management, operations and services to Malaysian pilgrims that have resulted in very important consequences for all aspects of the pilgrimage. The researcher adopts a qualitative method that enables her to analyse and assess the materials collected from multiple sources. These sources help furnish the study with solid accounts to examine the hajj management and its institution in Malaysia. The study concluded that on hajj management affairs, Tabung Haji serves as a strong platform for hajj candidates in fulfilling their aspiration to achieve haji mabrur (accepted hajj) through a variety of professional services. The corporation is also the only hajj public organization with statutory status in the world that provides comprehensive hajj facilities and hajj related services to Muslims making it as one of its kind in the world.